2020
DOI: 10.3389/fimmu.2020.01123
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Mouse FHR-1 Homolog, FHR-E, Accelerates Sepsis, and Acute Kidney Injury Through Enhancing the LPS-Induced Alternative Complement Pathway

Abstract: Alternative complement pathway (AP) plays an important role in the development of sepsis, which is life threatening. Deficiency of factor H-related protein 1 (FHR-1), which is a regulator of AP, has been considered as a susceptible factor for atypical hemolytic uremic syndrome (aHUS) and other types of nephropathy when an inducer such as infection exists. However, the underlying mechanism of the disease development is largely unknown. There is no report on CFHR1 gene knockout in any animal infection model and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Acute colon injury mice model was built by intraperitoneal injection (i.p.) with 10 mg/kg LPS (Sigma, Shanghai, China) for 24 h as described before ( 29 31 ). BRD4 inhibition was applied by i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Acute colon injury mice model was built by intraperitoneal injection (i.p.) with 10 mg/kg LPS (Sigma, Shanghai, China) for 24 h as described before ( 29 31 ). BRD4 inhibition was applied by i.p.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro , experiments show that FHR‐1 from stem cells protects the stem cells themselves as well as endogenous astrocytes (Shi et al, 2016). Very recently, Li, Hao, Liu, and Li (2020) reported that LPS infection significantly enhanced alternative pathway activity in a mouse model in which FHRE, the murine homologue of FHR‐1, had been knocked out. These data support a regulatory role for FHR‐1 during complement activation.…”
Section: Complement Activationmentioning
confidence: 99%
“…Three FHR proteins that are present in mice show a high degree of amino acid identity with mouse factor H (range, 85–100%) (Hellwage et al, 2006; Li, Hao, Liu, & Li, 2020) (Figure 4). The three proteins are termed FHRB, FHRE and FHRC.…”
Section: Mouse Factor H‐related Proteins (Fhrs)mentioning
confidence: 99%
“…More specifically, the mCFHR genes differ in structure, domain composition, and sequence from the human genes (32). Like the human FHR proteins, a total of five murine CFHR genes have been suggested (mCFHR-A, mCFHR-B, mCFHR-C, mCFHR-D and mCFHR-E) and evidence for four mFHR proteins (FHR-B, FHR-C, FHR-D and FHR-E) has been derived from mRNA transcripts isolated from mouse liver (48,(140)(141)(142)(143). However, altogether, this suggests that direct comparisons between the human and mouse FHR proteins is not informative and, therefore, any mouse FHR homologs need to be identified, if they exist, by functional studies before rodent models can be used to further study the role of the FH protein family in human health and disease.…”
Section: Limitations Of Animal Modelsmentioning
confidence: 99%